Psychological Analysis of Healthcare Workers During Covid-19 in Indonesia; Systematic Review and Meta-Synthesis - Ilmidin Ilmidin; Riza Nabila; Nina Sarasnita; Astika Candra Nirwana; Roviana Nurda Agustin (Jurnal Berkala Kesehatan, 2023)
Healthcare workers (HCw) are at the forefront of treating infectious diseases. The excessive workload on Covid-19 HCw adds to the level of fatigue and psychological burden that existed before the Covid-19 pandemic. HCw knowledge of the likelihood of infection can affect their mental and physical stress levels, so they will experience common symptoms including trauma, fear, anxiety, and insomnia caused by excessive fear of infection. This study aims to summarize most research articles that discuss the description and influence of psychology on health workers throughout Indonesia during the Covid-19 pandemic. This study uses a systematic method of qualitative review (meta-synthesis). High levels of stress, depression, anxiety, and insomnia symptoms were found in Indonesia. The results also showed the influence of gender, education, and contact with patients on the incidence of psychological problems in health workers. Providing positive support and preparing psychiatric personnel in hospitals and/or other healthcare settings can reduce the impact of psychology on healthcare workers.